Characteristics of plant communities, population features, and edaphic conditions of Arnica montana L. populations in pine forests of mid-Eastern Europe - Piotr Sugier; Danuta Sugier; Oleg Sozinov; Aleksander Kołos; Dan Wołkowycki; Andrzej Plak; Olha Budnyk (Acta Societatis Botanicorum Poloniae, 2019)
Mountain arnica, Arnica montana L., an herbaceous plant species critically endangered in Europe, is the source of raw material, which is abundant in its secondary metabolites. During the field investigation conducted in Augustów and Knyszyn forests (Poland) and in Grodno Forest (Belarus), the plant species composition and population characteristics were measured. Additionally, to evaluate the edaphic conditions of arnica populations, soil samples were taken and analyzed. The sandy and very nutrient-poor soils are characterized by strong acidity and a very low concentration of macro- and microelements. The analyzed characteristics of the studied populations indicate a good status of populations located in Grodno Forest. However, the very small number of individuals and the very small proportion of flowering individuals in the populations in Augustów Forest and Knyszyn Forest indicate the need for active protective actions. Calamagrostis arundinacea can play the role of a competitor; therefore, during planning active protection, individuals of this species should be eliminated, and particular attention should be paid to the frequency and coverage of this plant species and the plant height of the herb layer. The dependence between population characteristics, especially the proportion of flowering stems and the concentration of available phosphorus, may indicate the effect of the concentration of this macroelement on flowering and, in consequence, provide a greater chance for the generative propagation of this plant species.